Lack of agreement between different observers and methods in the measurement of capillary refill time in healthy volunteers: an observational study - Valenzuela Espinoza, E.D. (2014)
Objective: Peripheral perfusion abnormalities are relevant manifestations of shock. Capillary refill time is commonly used for their evaluation. However, the reproducibility of capillary refill time measurements and their correlation with other variables of peripheral perfusion, have not been comprehensively evaluated. Our goal was to determine, in healthy volunteers, the agreement between different methods of capillary refill time quantification and different observers, as well as their correlation with other markers of peripheral perfusion. Methods: We studied 63 healthy volunteers. Two observers measured capillary refill time by means of two methods, direct view (CRTchronometer) and video analysis (CRTvideo). We also measured perfusion index (PI) derived from pulse plethysmography and finger pad temperature (T°peripheral). The agreement between observers and methods was assessed using the Bland and Altman method. Correlations were calculated using Pearson's correlation. A p-value<0.05 was considered significant. Results: The 95% limits of agreement between the two observers were 1.9 sec for CRTchronometer and 1.7 sec for CRTvideo. The 95% limits of agreement between CRTchronometer and CRTvideo were 1.7 sec for observer 1 and 2.3 sec for observer 2. Measurements of CRTchronometer performed by the two observers were correlated with T°peripheral. Measurements of CRTvideo performed by the two observers were correlated with T°peripheral and perfusion index. Conclusion: In healthy volunteers, measurements of capillary refill time performed by either different observers or different methods showed poor agreement. Nevertheless, capillary refill time still reflected peripheral perfusion as shown by its correlation with objective variables of peripheral perfusion.